2012
DOI: 10.1029/2012jd018125
|View full text |Cite
|
Sign up to set email alerts
|

FY‐2C‐derived diurnal features of clouds in the southern contiguous China

Abstract: C and 0 C) reaches its diurnal maxima in the early evening to the midnight. The frequency of warm cloud (WC, defined as CTT warmer than 0 C) peaks around noon. There are also distinct regional differences of the diurnal variation of summer CC and MC frequencies. The diurnal variation of CC, MC and WC frequencies also show evident seasonal changes. The late afternoon peak of CC frequency appears in almost all months, and in the cold seasons, there is also a midnight to late evening secondary peak. The MC freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Peaks seldom occur before dawn or after midnight. This pattern, especially in southern China, is in good agreement with previous results from FY‐2 (e.g., Chen et al, ; Jin et al, ). Over ocean, most of the peaks unexpectedly appear in the late afternoon (Figure e), in particular in western Pacific Ocean, which agrees well with the diurnal cycle revealed from 10 year International Satellite Cloud Climatology Project (ISCCP) data (Feng & Fu, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Peaks seldom occur before dawn or after midnight. This pattern, especially in southern China, is in good agreement with previous results from FY‐2 (e.g., Chen et al, ; Jin et al, ). Over ocean, most of the peaks unexpectedly appear in the late afternoon (Figure e), in particular in western Pacific Ocean, which agrees well with the diurnal cycle revealed from 10 year International Satellite Cloud Climatology Project (ISCCP) data (Feng & Fu, ).…”
Section: Resultssupporting
confidence: 92%
“…Xi et al () used both Geostationary Operational Environmental Satellite observations and Atmospheric Radiation Measurement (ARM) data to derive 10 year climatology of cloud fraction (CF) and its vertical distribution. However, there are merely a few studies (e.g., Chen et al ; Jin et al, ) focused on clouds over China using geostationary satellites due to the limited spatiotemporal resolution of second‐generation Fengyun series (FY‐2). On a side note, the development of cloud products from FY‐4 is still undergoing and has recently made substantial advances as summarized in Min et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3a illustrates that the diurnal peak of the TC to the south of 20 • N appears in the afternoon (12-15 LST), which is closely related to the diurnal variation of convective clouds. Meanwhile, the diurnal peak of the TC at 20-26 • N (i.e., southern China) appears in two periods during the early morning (06-08 LST) and afternoon (11)(12)(13)(14)(15)(16). This is probably due to the diurnal peaks of Ac and Sc in these areas that occur in the early morning and evening and have a great impact on the diurnal variation of the TC occurrence frequency.…”
Section: Diurnal Variation Of Different Types Of Cloudsmentioning
confidence: 99%
“…The diurnal peaks of precipitation in South and Northeast China appear in the afternoon (16-17 LST) (Figure 6c,d). Although the peak precipitation between the Yangtze River valley and the Yellow River valley (region 5) differs among different stations (figure omitted), the diurnal variation of precipitation in this region is generally bimodal with peaks in the early morning (06-08 LST) and afternoon (16)(17)(18). By comparing our results with the diurnal variation characteristics of the precipitation in the five regions from 1991 to 2004 reported by Yu et al (Figure 2 in Yu's article), it is found that the hourly merged precipitation data can effectively reflect the diurnal variation of the precipitation in each region.…”
Section: Diurnal Variation Of Precipitationmentioning
confidence: 99%
See 1 more Smart Citation